The Effect of Using Think-Pair-Share in Teaching Present Tense to Second Semester Students of Indonesia Prima University (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
The objective of this study was to discover the significant effect of using think-pair-share in teaching present tense. The population of this research was the second semester students of Indonesia Prima University, academic year 2020/2020. The sample was 40 students; 20 students in the experimental group and 20 students in the control group. The data was collected by using a test. The instrument consisted of 40 items. The data were analyzed by using T-test formula. The findings indicate that using think-pair-share showed positive effect on the students’ learning achievement. It was proved from the result of the post test for the experimental group (78.5) is higher than the control group (55.25) and the result of t-test (4.42) was higher than the t-table (2.021) and level of significance (0.05) which means that the hypothesis stating that the students’ achievement taught by using think-pair-share was higher than the conventional method in teaching present tense was accepted. The conclusion is the t-observed is higher than t-table (4.42 > 2.021; p = 0.005). It means that students’ learning achievement taught by using think-pair-share is higher than the conventional method. So, English teachers/lecturers are suggested to apply think-pair-share in teaching present tense.